Can't Stand the Pressure: The Association Between Unprotected Standing, Walking, and Wound Healing in People With Diabetes. (July 2017) - Najafi, Bijan; Grewal, Gurtej S.; Bharara, Manish; Menzies, Robert; Talal, Talal K.; Armstrong, David G.
Objective: The objective was to report patterns of physical activity and their relationship to wound healing success in patients with diabetic foot ulcers protected with removable or irremovable offloading devices. Methods: Forty-nine people with diabetic foot ulcers were randomized to wear either a removable cast walker (RCW) or an irremovable instant total contact cast (iTCC). Primary outcome measures included change in wound size, physical activities including position (ie, sitting, standing, lying) and locomotion (speed, steps, etc). Outcomes parameters were assessed on weekly basis until wound healing or until 12 weeks. Results: A higher proportion of patients healed at 12 weeks in the iTCC group ( P = .038). Significant differences in activity were observed between groups starting at week 4. RCW patients became more active than the iTCC group (75% higher duration of standing, 100% longer duration of walking, and 126% longer unbroken walking bout, P < .05). Overall, there was an inverse association between rate of weekly wound healing and number of steps taken per day ( r < –.33, P < .05) for both groups. RCW patients had a significant inverse correlation between duration of daily standing and weekly rate of healing ( r = –.67, P < .05). Standing duration was the only significant predictor of healing at 12 weeks. Conclusion: The results from this study suggest significant differences in activity patterns between removable and irremovable offloading devices. These patterns appear to start diverging at week 4, which may indicate a decline in adherence to offloading. Results suggest that while walking may delay wound healing, unprotected standing might be an even more unrealized and sinister culprit.